Rethinking Oran Young's model for studying the effectiveness of international institutions: absorption and incorporation, and vulnerability as new variables - Sanches, Rafaela Resende (Sustainability in Debate, 2024)
This article proposes a theoretical reflection on the effectiveness of international institutions, expanding Oran R. Young's classic model and incorporating two new variables: “Absorption and Incorporation” and “Vulnerability”. Starting from a visit to the contributions of authors such as Duffield, Keohane and Nye on the subject, the work explores how the capacity of States to internalise institutional norms and rules, as well as their vulnerability to global problems, have a direct impact on the effectiveness of these institutions. Without claiming to be an immediate empirical analysis, the article offers a theoretical contribution to the field of International Relations, expanding Young's model and suggesting that future research apply these new variables in case studies. In doing so, it aims to advance the understanding of the mechanisms through which international institutions influence the behaviour of States and generate tangible results in global governance.